2006
DOI: 10.1021/la060486i
|View full text |Cite
|
Sign up to set email alerts
|

Modelization of the Release from a Tetradecane/Water/Hexadecane Multiple Emulsion: Evidence of Significant Micellar Diffusion

Abstract: The release of tetradecane from a multiple emulsion of the type tetradecane/water/hexadecane was studied experimentally using the differential scanning calorimetry technique. The kinetics of the tetradecane release was measured for three formulations containing different concentrations of hydrophilic surfactant (2%, 4%, and 7%). A new mass transfer model derived from the shrinking core model was developed. The values of the model parameters deduced from the least-squares fittings led to the determination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…For instance in the case of oil-in-water (O/ W) emulsions, these systems allow to model transport processes between two oil phases separated by an aqueous membrane [4][5][6][7][8][9][10][11][12][13][14]. Other types of emulsions, as water-in-oil emulsions [13,[15][16][17][18] or oil-water-oil (O/W/O) and water-oil-water (W/O/W) multiple emulsions have also been used in this purpose [13,[19][20][21][22][23][24][25]. Different transfer mechanisms have been reported, including solution-diffusion [15] or micelle-facilitated transport [4][5][6][7][9][10][11]13,14,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance in the case of oil-in-water (O/ W) emulsions, these systems allow to model transport processes between two oil phases separated by an aqueous membrane [4][5][6][7][8][9][10][11][12][13][14]. Other types of emulsions, as water-in-oil emulsions [13,[15][16][17][18] or oil-water-oil (O/W/O) and water-oil-water (W/O/W) multiple emulsions have also been used in this purpose [13,[19][20][21][22][23][24][25]. Different transfer mechanisms have been reported, including solution-diffusion [15] or micelle-facilitated transport [4][5][6][7][9][10][11]13,14,25].…”
Section: Introductionmentioning
confidence: 99%
“…Other types of emulsions, as water-in-oil emulsions [13,[15][16][17][18] or oil-water-oil (O/W/O) and water-oil-water (W/O/W) multiple emulsions have also been used in this purpose [13,[19][20][21][22][23][24][25]. Different transfer mechanisms have been reported, including solution-diffusion [15] or micelle-facilitated transport [4][5][6][7][9][10][11]13,14,25]. In these systems, surfactant molecules are involved in the different steps of the experiment: first in the emulsion formation, the decrease in interfacial tension induced by the surface active molecules affecting the droplets formation and their break-up process, secondly in the stabilization of the emulsion by the formation of an adsorbed film at the oil droplet/water interface, and then in the oil transfer process by modifying the solubility of oil in the aqueous phase, which may involve (or not) the solubilization of oil in micelles.…”
Section: Introductionmentioning
confidence: 99%
“…A theoretical analysis has shown that the mass transfer occurs essentially by micellar diffusion [77].…”
Section: Mass Transfer Within Multiple Emulsionsmentioning
confidence: 99%
“…Pickering emulsions with graphene oxide (GO) as a stabilizer had been prepared and the effects of the type of oil, the sonication time, the GO concentration, the oil/aqueous rate, and the pH value on the stability, type, and morphology of the systems were investigated [24]. And multiple emulsions with different oils including camelina, fish, camelinae and fish oil blends and lipophilic polyglycerol polyricinoleate (PGPR) and hydrophilic sodium caseinate (SC) as emulsifiers had also been investigated [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, the stable of multiple emulsions still unsettled, whether prepared by two-step or single-step emulsification with different emulsifiers and oils [24][25][26].…”
Section: Introductionmentioning
confidence: 99%